PERANCANGAN APLIKASI CLOUD DRIVE BERBASIS WEB SEBAGAI MEDIA PENYIMPANAN ONLINE MENGGUNAKAN VIRTUAL PRIVATE SERVER - Entik Insanudin; Anang Sularsa; Duddy Soegiarto (Universitas Widyatama, 2024)
The technology that is developing today is information technology. The more storage media used by the public, one of the most widely used media today is cloud-based storage media. The creation of this Cloud Drive application can be done by file sharing using a Virtual Private Server. The server used is the Debian 8 server. The Debian 8 server is an open source server developed on the Linux operating system to serve data exchange between Linux and Windows which will be used on the virtual private server. Thus, making it easier for administrators to configure. In this way, this application can become one of the successful storage media that can be easily accessed by the general public to store any data. Keywords : Cloud Drive, UBuntu, Storage Media, Website